PENERAPAN PEMBELAJARAN MULTIMEDIA SEBAGAI INOVASI PEMBELAJARAN PADA TK PKK KALITIRTO BERBAH: Application Of Multimedia Learning As A Learning Innovation In PKK Kindergarten Kalitirto Berbah - Kharisma, Rizqi Sukma (Jurnal Pengabdian Masyarakat Kesehatan, 2019)
Information technology has penetrated into all lines of life both for economic, social and educational needs. In the education sector technology is used for the needs of supporting the teaching and learning process and also used for school management. PKK Kindergarten Kalitirto is one of the places for early education in the Berbah sub-district, Sleman district. With the rapid development of technology at this time, PKK Kindergarten Kalitirto is still quite behind in terms of the facilities used. On the teaching and learning activities PKK Kindergarten Kalitirto also wants to have multimedia learning in addition to the existing manual learning media. However, due to budget constraints where the average parents of Kalitirtio PKK Kindergarten students are in the middle to lower economic class, the procurement of multimedia learning is considered quite difficult. From the problems mentioned above, in this service the provision of multimedia-based learning facilities and training in their use are carried out. It is hoped that PKK Kindergarten Kalitirto teachers can independently use existing multimedia learning for teaching and learning activities.